SERVQUAL PRAMUGRAHA DALAM PENYIAPAN KAMAR DI DESA WISATA - I Wayan Pantiyasa; Ni Putu Diah Prabawati (Jurnal Ilmiah Hospitality Management, 2014)
Â The purpose of this research is to know the quality of room preparation qualitiy to the guest at the tourism village, Pinge. Data analysis technique which is used is quantitative descriptive analysis technique with SevQual method and importance Performance Analysis (IPA). The result of the analysis which is done by ServQual method if the daifference of the prospect level average and the implementation level average is 0,01, it means very satisfying. While the analysis which is used by Importance â€“ Performance Analysis (AIPA) it is known that from 16 service quality indicator, there are 2 indicators that are very important for the guest but the implementation by the attendant is not satisfied yet and it is on quadrant A (main priority). There are 4 indicators which are on quadrant B (keep the performance) that show the main service element is successfully done by the attendant, so it has to keep up. There are 2 indicators on quadrant C (low priorty) that show some the influence of the indicators are not important but the implemntation by the attendant 13 is not satisfied yet. While there are 6 indicators on quadrant (excessive) that show the less important indicators influencing the guest but the implementation is excessive.